Perlindungan Hukum terhadap Korban Jalan Berlubang di Tol Palembang-Lampung - Alfa Rizqie Ramadhan, Aselino; Suharno, Suharno; Dewi, Nourma (Dinasti Review Publisher, 2024)
This study aims to analyze the legal protection provided to victims of accidents caused by potholes on the Palembang-Lampung toll road. The research method used is descriptive with a qualitative approach, involving analysis of legal documents, interviews, and field observations. The results show that the losses suffered by victims due to potholes on the road do not always receive adequate compensation in accordance with the losses suffered. Legal protection for victims is still limited and not optimal, especially in terms of fulfilling the rights of victims to compensation and rehabilitation. Improvements in the legal system and law enforcement are needed to ensure that victims of potholes receive legal protection in accordance with their rights. This is important to improve road safety and justice for accident victims